2018
DOI: 10.1155/2018/5129421
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Macroinvertebrates Diversity as Bioindicator of Water Quality of Some Rivers in East Kalimantan, Indonesia

Abstract: The objectives of this study were to clarify and evaluate the water quality of a number of rivers in East Kalimantan province of Indonesia. For this purpose, our study successfully utilized the benthic macroinvertebrates diversity as well as physicalchemical parameters of river's water. For instance, based on the values of Average Score per Taxon (ASPT) and the National Sanitation Foundation-Water Quality Index (NSF-WQI), Karang Mumus River was categorized as polluted with Chironomus sp. and Melanoides tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…The index ranges from 1 to 15. Thus, intact condition class (10)(11)(12)(13)(14)(15): areas dominated by different vegetation strata that cover the full length of the segment, which is linked to natural fluvial forms and slightly fragmented; moderately disturbed condition class (7-9): areas with vegetation cover nearly half of the study zone being disturbed, 1-3 m active channel width and about 10-30% exotic and ruderal species present. Severely disturbed condition class (1-6): areas where 60% of the riparian corridor is reduced by human-led activities, vegetation covering <30% (mainly grasses/herbs and isolated woody species) with channel banks connected to agricultural fields.…”
Section: Classification Of the Sampling Sites On The Riparian Zonementioning
confidence: 99%
See 1 more Smart Citation
“…The index ranges from 1 to 15. Thus, intact condition class (10)(11)(12)(13)(14)(15): areas dominated by different vegetation strata that cover the full length of the segment, which is linked to natural fluvial forms and slightly fragmented; moderately disturbed condition class (7-9): areas with vegetation cover nearly half of the study zone being disturbed, 1-3 m active channel width and about 10-30% exotic and ruderal species present. Severely disturbed condition class (1-6): areas where 60% of the riparian corridor is reduced by human-led activities, vegetation covering <30% (mainly grasses/herbs and isolated woody species) with channel banks connected to agricultural fields.…”
Section: Classification Of the Sampling Sites On The Riparian Zonementioning
confidence: 99%
“…Being a refugium for many invertebrates [ 7 ], fragmentation of riparian zones, following disturbances such as farming practices, grazing, and logging, could potentially reduce their habitats into narrow ranges and consequently affect community structure. Ecologists have used terrestrial invertebrates as indicators of ecological condition or stream biological integrity due to their high sensitivity to disturbances and wide distribution [ 8 , 9 , 10 ]. A study has revealed about 45% reduction in global terrestrial invertebrate population in the current Anthropocene epoch, which could likely cascade onto ecosystem functioning and human well-being [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Shannon diversity index (H'), richness index (C), and evenness index (E) are widely used to predict aquatic environmental conditions based on the biological components (Maneechan and Prommi 2015;Patang et al 2018). The higher Shannon diversity index means, the better the quality of water: the value of H' smaller than one indicates high water pollution, between one and three moderate pollutions and greater than four no pollution (Wilhm and Dorris 1968).…”
Section: Measurement Of Ecological Indicators Of River Water Qualitymentioning
confidence: 99%
“…Resident aquatic biota, including microorganisms, phytoplankton, zooplankton, macroinvertebrates, and fish are widely used to monitor the levels of freshwater pollution worldwide (Arimoro, Ikomi, Nwadukwe, Eruotor, & Edegbene, 2014;Patang, Soegianto, & Hariyanto, 2018). Among aquatic biota used in monitoring freshwater ecosystems, phytoplankton are primary producers, and therefore they constitute the base of aquatic food webs underpinning reservoir ecosystem stability and function (Geider et al, 2001).…”
Section: Introductionmentioning
confidence: 99%